СУЧАСНИЙ СТАН ОРГАНІЗАЦІЇ ЕКОЛОГІЧНИХ ТА АГРОРЕКРЕАЦІЙНИХ ПОСЕЛЕНЬ ТА ПЕРСПЕКТИВИ ЇХ РОЗВИТКУ (World Science, 2018)
The article is devoted to the study of existing ecological settlements with agro-recreational function in domestic and foreign practice, which are an integral part of recreational areas and are in interaction with all components of the recreational environment.In modern conditions, urbanization has become more global. Growth of settlements, increasing the proportion of urban population, as well as the emergence of more complex networks and systems of cities - has led to an expansion of the habitats of the urban environment and their qualitative changes.Agri-environmental use in modern conditions of sustainable development should ensure not only ecological food products for the population, but also guarantee the ecological development of the agro- industrial complex at the economic and urban levels, without prejudice to the natural environment.The solution of the problem in general is to create agro-recreational ecological settlements for their inclusion in recreational systems, by creating agrarian landscapes, using the main recreational resources of urban and rural areas such as climate, microclimate, relief, surrounding landscapes, etc.